Thermo-Mechanical Fatigue Crack Growth and Phase Angle Effects in Ti6246 - Jennie Palmer (Materials, 2022)
A bespoke TMF crack growth test set-up has been developed and validated for use throughout this study and the effects of phasing between mechanical loading and temperature have been investigated. The study shows that TMF cycles may show increased crack growth rate behaviour when compared to isothermal fatigue. The phase angle of the applied TMF cycle can also affect crack growth behaviour, with in-phase (IP) test conditions showing faster crack growth rates than out-of-phase (OP) test conditions. Propagating cracks interact with the microstructure of the material, in particular, the α/β interfaces within the prior beta grains and supporting fractography evidences subtle differences in fracture mechanisms as a result of phase angle.